2021
DOI: 10.1021/acs.est.1c00020
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Electron-Transfer Mechanism of Permanganate Activation by Graphite for Enhanced Oxidation of Sulfamethoxazole

Abstract: Many reagents as electron sacrificers have been recently investigated to induce decomposition of permanganate (KMnO 4 ) to produce highly reactive intermediate Mn species toward oxidation of organic contaminants; however, this strategy meanwhile causes low KMnO 4 utilization efficiency. This study surprisingly found that graphite can mediate direct electron transfer from organics (e.g., sulfamethoxazole (SMX)) to KMnO 4 , resulting in high KMnO 4 utilization efficiency, rather than reductive sites of graphite-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(62 citation statements)
references
References 36 publications
(62 reference statements)
2
49
0
Order By: Relevance
“…According to the theory of the Fukui function on nonradical oxidation processes, the local descriptors of f + and f − were adopted to distinguish the most vulnerable sites with respect to the nucleophilic and electrophilic reactions, respectively. 47…”
Section: Resultsmentioning
confidence: 99%
“…According to the theory of the Fukui function on nonradical oxidation processes, the local descriptors of f + and f − were adopted to distinguish the most vulnerable sites with respect to the nucleophilic and electrophilic reactions, respectively. 47…”
Section: Resultsmentioning
confidence: 99%
“…Notably, when BC and KMnO 4 were injected into sulfamethoxazole solution, sulfamethoxazole could be rapidly and effectively removed within 30 min (97%). Likewise, Peng et al 288 reported that with the assistance of graphite, the oxidation ability of KMnO 4 -based AOPs would be boosted. In their study, the graphite mediated one-electron transfer from sulfamethoxazole to KMnO 4 led to high KMnO 4 utilization efficiency.…”
Section: Degradation Of Antibiotics By Metal-free Catalyzed Aopsmentioning
confidence: 99%
“…Notably, when BC and KMnO 4 were injected into sulfamethoxazole solution, sulfamethoxazole could be rapidly and effectively removed within 30 min (97%). Likewise, Peng et al 288 reported that with the assistance of graphite, the oxidation ability of Fig. 13 Second-order rate constants (k) for reactions of various antibiotics and commonly used quenching agents with ROS (i.e., cOH, SO 4 c À , 1 O 2 , and Clc).…”
Section: Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, advanced oxidation processes (e.g., Fenton technology [11], Fenton-like technology [12], ozone oxidation technology [13], permanganate oxidation technology [14], and photocatalytic technology [15]) have attracted considerable attention from researchers as methods for the degradation of such bio-refractory organic pollutants. In particular, permanganate oxidation technology has been widely utilized for the elimination of organic pollutants due to its advantages as a low-cost, easily transportable, and environmentally friendly methodology [16]. However, the stability of permanganate (PM, E 0 = 1.68 eV) and its low potential relative to radicals [17] to a certain extent limit its reactivity to organic pollutants.…”
Section: Introductionmentioning
confidence: 99%